Outer Space Treaty reform and the long-term sustainability of space exploration - Nahtigal, Matjaž (Teorija in praksa, 2022)
The challenge of ensuring the space environment’s long-term sustainability in the context of the exploration and commercialisation of outer space raises several important issues and dimensions with respect to both international environmental law and sustainable development. The research question analyses the extent to which such exploration benefits humanity and expands the province of all humankind. In this article, historical achievements of the international legal framework governing the area of space exploration are presented. Opportunities for further developing and strengthening this framework to ensure the cooperative, transparent, inclusive and equitable development of space exploration are deliberated, notably those that do not limit the interests and opportunities of space-faring countries. The key finding and proposition of this article is that while discussing the need to improve and strengthen the international regulatory framework, developing countries’ needs and interests should also be effectively incorporated. More equitable, inclusive and sustainable development is as much in the interest of developed countries as it is of developing countries.
Keywords: komercializacija vesolja; mednarodno pravo okolja; Odkritja in raziskovanja (astronavtika); pogodba o vesolju; Pogodbe (mednarodno pravo); raziskovanje vesolja; Trajnostni razvoj; trajnostno raziskovanje; Vesoljsko pravo